2013
DOI: 10.1021/ja4053398
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Size and Properties of ClyA Nanopores Assisted by Directed Evolution

Abstract: Nanopores have recently emerged as powerful tools in single-molecule investigations. Biological nanopores, however, have drawbacks, including a fixed size and limited stability in lipid bilayers. Inspired by the great success of directed evolution approaches in tailoring enzyme properties, in this work we evolved Cytolysin A from Salmonella typhi (ClyA) to a high level of soluble expression and desired electrical properties in lipid bilayers. Evolved ClyA nanopores remained open up to -150 mV applied potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
258
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(269 citation statements)
references
References 62 publications
11
258
0
Order By: Relevance
“…However, 5-15 min after the addition of the Aβ42 oligomers to the chamber, step-wise changes in bilayer conductance were observed ( Fig. 2A), behavior typical of the incorporation of individual proteins that form nanopores in membrane bilayers (21). As these oligomers induced various types of nanopore-like behavior, we grouped the responses into three classes, denoted type 1, 2, and 3 on the basis of the signal observed (Fig.…”
Section: The Aβ42 Oligomers Stabilized By Dpc Micelles Insert Into LImentioning
confidence: 99%
“…However, 5-15 min after the addition of the Aβ42 oligomers to the chamber, step-wise changes in bilayer conductance were observed ( Fig. 2A), behavior typical of the incorporation of individual proteins that form nanopores in membrane bilayers (21). As these oligomers induced various types of nanopore-like behavior, we grouped the responses into three classes, denoted type 1, 2, and 3 on the basis of the signal observed (Fig.…”
Section: The Aβ42 Oligomers Stabilized By Dpc Micelles Insert Into LImentioning
confidence: 99%
“…Recently we have shown that folded proteins might be trapped transiently inside the lumen of the Cytolysin A (ClyA) nanopore without the need of complex immobilization strategies or covalent chemistry. [25][26][27][28] Remarkably, ionic current recordings could monitor the binding of ligands to internalised proteins, indicating that an enzymatic activity can be translated into an electrical signal. 28 Conveniently, ClyA could be isolated in different oligomeric states, providing nanopores with identical chemical composition but different pore dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] We have shown that ClyA nanopores can be engineered to selectively internalize proteins into the nanopore interior. [25][26][27][28] Therefore, if proteins translocate through the nanopore under physiological conditions of ionic strength and applied potential, ClyA might be used to convey therapeutic proteins across biological membranes. Proving the translocation of proteins across nanopores, however, is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that these nanopores can be rendered capable of detecting selective cognate protein analytes by the attachment of appropriate aptamers at the pore mouth. In a separate study, 36 they used a directed evolution approach to tune the size and properties of ClyA nanopores. Meervelt et al 37 used the ClyA pore to investigate the interaction between the thrombin binding aptamer and human thrombin.…”
Section: Introductionmentioning
confidence: 99%